Metode Pembelajaran dengan Media Lagu untuk Meningkatkan Minat Belajar Firman Tuhan - Pangemanan, Like; Febriyona, Cristie; Supartini, Tri (Jurnal Jaffray, 2019)
The purpose of this paper is to apply learning methods with song media to increase interest in learning God’s word. The method used is qualitative, namely observation, interviews with research subjects. The conclusion of this study is 1) the method of song in learning for children aged 6-8 years should be made simple with a choice of interval notes 1-5 and using an agile rhythm so that children are easier and interested in learning it; 2) children’s learning interest to learn the Word of God, children need to have an interest in learning so that children can have an urge in themselves to learn God’s Word; 3) study of learning methods with songs on the interest in learning the Word of God can enhance children’s attention to learning, make children feel happy when learning, and the involvement of children is also quite active in learning.